Deep Aphantasia: a visual brain with minimal influence from priors or inhibitory feedback? - Bouyer, Loren N.; Arnold, Derek H. (Frontiers in Psychology, 2024)
The authors are both self-described congenital aphantasics, who feel they have never been able to have volitional imagined visual experiences during their waking lives. In addition, Loren has atypical experiences of a number of visual phenomena that involve an extrapolation or integration of visual information across space. In this perspective, we describe Loren’s atypical experiences of a number of visual phenomena, and we suggest these ensue because her visual experiences are not strongly shaped by inhibitory feedback or by prior expectations. We describe Loren as having Deep Aphantasia, and Derek as shallow, as for both a paucity of feedback might prevent the generation of imagined visual experiences, but for Loren this additionally seems to disrupt activity at a sufficiently early locus to cause atypical experiences of actual visual inputs. Our purpose in describing these subjective experiences is to alert others to the possibility of there being sub-classes of congenital aphantasia, one of which—Deep Aphantasia, would be characterized by atypical experiences of actual visual inputs.